2020
DOI: 10.1016/j.ausmj.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Would you like to shop via mobile app technology? The technology acceptance model, social factors and purchase intention

Abstract: This study investigates how technology acceptance model (TAM) factors and social factors determine customer purchase intention. Although previous studies on mobile apps have investigated TAM, critical social factors have been neglected, thus, reinforcing the need to study the latter's contribution to consumer purchase intention. Accordingly, this study examines social influence and peer influence in the TAM and collects 777 questionnaires from Digikala app users. Data were then analysed using structural equati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(178 citation statements)
references
References 89 publications
(128 reference statements)
12
154
0
12
Order By: Relevance
“…Accordingly, for each type of benefit, this study focuses on a selection of typical benefits that past studies have recurrently examined. For example, for the utilitarian benefits, this study focuses on ease of use and usefulness, which are well-known drivers of technology acceptance and use (e.g., Byun et al, 2018;Vahdat, Alizadeh, Quach, & Hamelin, 2020;Veríssimo, 2018); it also considers practical relevance (or interpersonal utility), given its documented impact on the intention to use apps (e.g., Stocchi, Michaelidou, & Micevski, 2019). In terms of hedonic benefits, this study concentrates on selfenhancement (e.g., Scholz & Duffy, 2018;Zhu, So, & Hudson, 2017), entertainment (e.g., Gao, Rohm, Sultan, & Pagani, 2013;van Noort & van Reijmersdal, 2019), and the visual (or aesthetic) appeal/layout of the app (e.g., Kumar et al, 2018).…”
Section: The Evaluative Pathmentioning
confidence: 99%
“…Accordingly, for each type of benefit, this study focuses on a selection of typical benefits that past studies have recurrently examined. For example, for the utilitarian benefits, this study focuses on ease of use and usefulness, which are well-known drivers of technology acceptance and use (e.g., Byun et al, 2018;Vahdat, Alizadeh, Quach, & Hamelin, 2020;Veríssimo, 2018); it also considers practical relevance (or interpersonal utility), given its documented impact on the intention to use apps (e.g., Stocchi, Michaelidou, & Micevski, 2019). In terms of hedonic benefits, this study concentrates on selfenhancement (e.g., Scholz & Duffy, 2018;Zhu, So, & Hudson, 2017), entertainment (e.g., Gao, Rohm, Sultan, & Pagani, 2013;van Noort & van Reijmersdal, 2019), and the visual (or aesthetic) appeal/layout of the app (e.g., Kumar et al, 2018).…”
Section: The Evaluative Pathmentioning
confidence: 99%
“…Setelah mereka mendapatkan pengalaman dari kemudahan menggunakan situs, kualitas informasi yang baik seperti kejelasan informasi, informasi yang relevan, tepat waktu, maka akan terbentuk rasa kepuasan secara elektronik yang ditunjukkan dengan kesediaan mereka dalam membagikannya kepada konsumen lain. Dari [14], [71], [46], [41], [72], [18], [40], [73], [15], [74], [63], [23], [71], [59], [75], [40], [17] 3 SEM [65], [14], [41], [66], [32], [76], [51], [64], [56], [60], [47], [3], 4…”
Section: B Bagaimana Gambaran Mengenai Perilaku Konsumen Danunclassified
“…Extensions of TAM including variables such as self-identity (Lee et al, 2006) and social and peer influence (Malhotra & Galletta, 1999;Vahdat et al, 2020) have found that these social factors influence attitude towards technology and acceptance of technology. In addition, TAM2 that incorporates other theoretical constructs to TAM discovered that social influence processes (subjective norm, voluntariness, and image) and cognitive processes (relevance of job, output quality, result demonstrability, and perceived ease of use) influence user's acceptance of technology (Venkatesh & Davis, 2000).…”
Section: Limitationsmentioning
confidence: 99%